ANALISIS SEKTOR UNGGULAN DI KABUPATEN MALINAU - Darmawanto, Agus Tri; Mufidah, Annisa (JURNAL EKONOMI PEMBANGUNAN, 2024)
The aim of this research is to determine the leading sectors in Malinau Regency, North Kalimantan Province. Type of quantitative descriptive research. The data used is secondary data obtained from the Malinau Regency Central Statistics Agency. The data uses Gross Regional Domestic Product Based on Constant Prices for Malinau Regency from 2019 to 2023. The analysis uses LQ, Shift Share and Klassen Typology. The research results show that the leading sectors of Malinau Regency include the mining and quarrying sector, the water supply; sewerage, waste management, remediation activities sector, the construction sector, the accommodation and food service activities sector, and the public administration and defence and compulsory social security sectors. Klassen Typology Analysis shows that the sectors that are in the advanced and rapidly growing category are the mining and quarrying sector, the water supply; sewerage, waste management, remediation activities sector, the construction sector, the accommodation and food service activities sector, and the public administration, and defence and compulsory security sectors. Shift Share analysis shows that the total positive net shift value (Dij) indicates economic progress and economic growth in Malinau Regency. This means that the mining and quarrying sector has the highest contribution compared to other economic sectors.